Prevalence of latent acidotic stress in dairy cows in the Sanliurfa region - Dincer, Pelin Fatos Polat; Gul, Yusuf (Polish Soc Veterinary Sciences Editorial Office, 2020)
This study aimed to determine the incidence of latent acidotic stress (LAS), which is an important problem in dairy cow breeding in Turkey, to investigate net acid-base excretion in urine, and to provide veterinary doctors with information about the early diagnosis and treatment of LAS. Two study groups were formed according to the rumen fluid pH values: LAS group (19 cows) with 5.2 < pH < 6.0 (19 cows) and healthy group (81 cows) with 6.0 < pH < 7.2. Blood, urine and ruminal fluid samples were taken after a general clinical examination of the animals. The physical properties of the rumen fluid, methylene blue reduction time, total infusoria number, and volatile fatty acid (VFA) amounts were determined. In addition, examinations of blood gases, urine pH, and net acid-base excretion (NABE) were performed. The general physical examination did not reaveal any statistically significant difference in the body temperature between the LAS group (n = 19) and the control group (n = 81) (p = 0.614), but a significant increase in the heartbeat, respiratory frequency, and the number of rumen movements was observed in the LAS group (p = 0.001). The following findings were observed in the rumen fluid from cows of the LAS group: decreased methylene blue reduction time (p = 0.001), decreased pH (p = 0.001) and infusoria density (p = 0.001), increased sedimentation time (p = 0.001) and total VFA amount (p = 0.001), no flotation. Compared with the healthy cows, the LAS group showed decreased blood pH (p = 0.001) and oxygen pressure (pO(2)) (p = 0.001), increased carbon dioxide pressure (pCO(2)), base excess (BE) and bicarbonate (HCO3) values (p = 0.001), and decreased urine pH (p = 0.001) and net acid-base excretion (p = 0.001) values. The incidence of latent acidotic stress in dairy cows in the Sanliurfa region was determined as 19%. In addition, it was concluded that net acid-base excretion values in urine can be used as an auxiliary parameter in the diagnosis of LAS and can be easily applied in the field.
Keywords: latent acidotic stress; dairy cow; acidotic overload